Functional lesional neurosurgery for tremor: back to the future?. Issue 7 (21st December 2017) - Schreglmann, Sebastian R; Krauss, Joachim K; Chang, Jin Woo; Martin, Ernst; Werner, Beat; Bauer, Ronald; Hägele-Link, Stefan; Bhatia, Kailash P; Kägi, Georg
Abstract : For nearly a century, functional neurosurgery has been applied in the treatment of tremor. While deep brain stimulation has been in the focus of academic interest in recent years, the establishment of incisionless technology, such as MRI-guided high-intensity focused ultrasound, has again stirred interest in lesional approaches. In this article, we will discuss the historical development of surgical technique and targets, as well as the technological state-of-the-art of conventional and incisionless interventions for tremor due to Parkinson's disease, essential and dystonic tremor and tremor related to multiple sclerosis (MS) and midbrain lesions. We will also summarise technique-inherent advantages of each technology and compare their lesion characteristics. From this, we identify gaps in the current literature and derive future directions for functional lesional neurosurgery, in particularly potential trial designs, alternative targets and the unsolved problem of bilateral lesional treatment. The results of a systematic review and meta-analysis of the consistency, efficacy and side effect rate of lesional treatments for tremor are presented separately alongside this article.